Strategi Pengembangan Usaha Alat Sterilisasi Buah Menggunakan Ozone-Box - Sholihah Ayu Wulandari; Sekar Ayu Wulandari; Ahmad Haris Hasanuddin Slamet; Ahmad Fahriyannur Rosyady; Rahmat Dhandy (Food Scientia : Journal of Food Science and Technology, 2022)
An ozone-box sterilizer is a tool used for the fruit sterilization process using ozone technology, in which ozone is already effective in dealing with microbial and chemical contamination. Competition in the business environment is getting tighter, therefore, an ozone-box fruit sterilizer business must develop its business to survive and be able to compete in the market. The purpose of this research is to identify and analyze the internal and external factors of the fruit sterilization equipment business using the ozone box, which is then used as a reference in determining business strategy. The research method used was a descriptive study using a SWOT analysis (strength, weakness, opportunities, and threats) related to developing an ozone-box-based fruit sterilization equipment business. The data used in this study consisted of primary data and secondary data, namely observational data on ozone sterilizers and interview data with experts. The study results show that the ozone-box product business is in Quadrant II, namely the quadrant between strengths and threats (Strength – Threat) and conducting socialization on ozone technology for fruit sterilization, product positioning as needed, and conducting regular research to update the technology used.